THE DEVELOPMENT OF THE SOCIAL COMMUNITY SYSTEM OF THE ASTRONOMER AND THE SCIENTISTS WHO CONTRIBUTED TO IT - O‘rinboyeva , Kumushoy Sultonbekovna; Mahmudova, Gulzeboxon (Educational Research in Universal Sciences, 2023)
In the article, I will write about the development of astronomy in the process of social society, about the universe and our current place in it, about the attention, actions and activities of the social community towards this science. During this period, important changes in astronomy can be seen. It is stated that it was done. In addition, great astronomers and physicists contributed their parts to the social community system for the further development of the science of astronomy.